ОБ АСИМПТОТИЧЕСКОМ РЕШЕНИИ ЗАДАЧИ ТЕРМОУПРУГОСТИ ДЛЯ ИЗОТРОПНЫХ ПЛАСТИН - Р. С. Геворкян (National Academy of Sciences of Armenia)
The asymptotic method of the solution of boundary value problem of elasticity theory is effective for anisotropic plates and shells with the kinematical and mixed boundary conditions [1-3]. In this work the asymptotic method is applied for the solution of connected dynamic problems of thermoelasticity for plates, at first represented all components of stress tensors and transfer vector with its Fourier transformation images.
Keywords: Thin bodies, structures; Mechanics of deformable solids